(untitled) (Eurasian Journal of Philology Science and Education, 2016)
Distance learning is a form of education in which the main elements include physical separation of teachers and students during instruction and the use of various technologies to facilitate student-teacher and student-student communication. Paced delivery is currently the most common mode of distance education delivery. Alternatively, some institutions offer self-paced programs that allow for continuous enrolment and the length of time to complete the course is set by the learner’s time, skill and commitment levels. Paced courses may be offered in either synchronus mode, but self-paced courses are almost always offered asynchronously. Each delivery model offers both advantages and disadvantages for students, teachers and institutions. Paced models are a familiar mode as they are used almost exclusively in campus based schools. Institutes that offer both distance and campus programs usually use paced models as teacher workload, student semester planning, tuition deadlines, exam schedules and other administrative details can be synchronized with campus delivery. Student familiarity and the pressure of deadlines encourage students to readily adapt to and usually succeed in paced models. Finally, paced models allow students to readily form communities of inquiry and to engage in collaborative work.